Rethinking organization theory: The fold, the rhizome and the seam between organization and the literary - Pick, David (The International Society for Organization Development, 2017)
© 2016, © The Author(s) 2016. The aim of this article is to apply literary theory and a work of literary fiction (Cloud Atlas by David Mitchell) to the task of offering points of departure for new thinking about organization theory. To this end, I locate this article at the seam between organization and the literary, where I employ two concepts proposed by Deleuze (the fold and the rhizome), apply the semiotic square and discuss the relationship between form and content. An examination of Cloud Atlas is positioned in the middle of the article to reflect the idea that the literary is at the heart of organization and vice versa. In keeping with the literary spirit of Cloud Atlas, this article mirrors the following narrative pattern of the novel: A | B | C | D | C | B | A. By working the seam, I find a way of developing alternative metaphors, challenging prevailing ideological assumptions and problematizing current paradigm assumptions.